Сучасна українська інтернет-археографія: основні форми та джерела електронних публікацій - Папакін, Г.В. (Український історичний журнал, 2010)
Уперше робиться спроба проаналізувати основні форми представлення історичних джерел в українському сеґменті ґлобального інформаційного простору, що є предметом інтернет-археографії – спеціального розділу відповідної науки. Подається класифікація основних типів інтернет-публікацій, докладно розглядаються види електронної археографічної продукції: бібліотека, збірник документів, навчальна хрестоматія. The author made an attempt to analyse the basic forms of presentation of historical sources in the Ukrainian segment of the Internet which is the subject of the special section of archaeography science as Internet-archaeography. Classification of basic types of Internet publications is given, three types of archaeographic products are thoroughly examined: electronic library, electronic document edition and educational reading-book.